2023
DOI: 10.1088/1367-2630/ad016f
|View full text |Cite
|
Sign up to set email alerts
|

Amplitude-dependent edge states and discrete breathers in nonlinear modulated phononic lattices

Matheus I N Rosa,
Michael J Leamy,
Massimo Ruzzene

Abstract: We investigate the spectral properties of one-dimensional spatially modulated nonlinear phononic lattices, and their evolution as a function of amplitude. In the linear regime, the stiffness modulations define a family of periodic and quasiperiodic lattices whose bandgaps host topological edge states localized at the boundaries of finite domains. With cubic nonlinearities, we show that edge states whose eigenvalue branch remains within the gap as amplitude increases remain localized, and therefore appear to be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 72 publications
(135 reference statements)
0
5
0
Order By: Relevance
“…A transition from edge to bulk in an elastic TI by increasing the excitation amplitude was experimentally demonstrated [39]. In addition, topological phase transition [40], self-tunability [41], edge solitons [42], discrete breathers [45], nonlinear harmonic generation [43,46], instability [44,47], and thermalization [48] were reported in nonlinear elastic TIs. However, these works are limited to the traditional first-order TIs, whilst nonlinear elastic HOTIs remain largely unexplored.…”
Section: Introductionmentioning
confidence: 93%
See 4 more Smart Citations
“…A transition from edge to bulk in an elastic TI by increasing the excitation amplitude was experimentally demonstrated [39]. In addition, topological phase transition [40], self-tunability [41], edge solitons [42], discrete breathers [45], nonlinear harmonic generation [43,46], instability [44,47], and thermalization [48] were reported in nonlinear elastic TIs. However, these works are limited to the traditional first-order TIs, whilst nonlinear elastic HOTIs remain largely unexplored.…”
Section: Introductionmentioning
confidence: 93%
“…To investigate the nonlinear effect, we employ a special version of the Galerkin method-HBM-to calculate the band structure of the lattice. It has been shown that HBM is effective in studying 1D nonlinear elastic TIs [39,45], even for elastic wave propagation in strongly nonlinear periodic structures [52]. Based on HBM, we develop a method to characterize the higher-order band topology in the nonlinear regime.…”
Section: Nonlinear Higher-order Band Topologymentioning
confidence: 99%
See 3 more Smart Citations